Effectiveness, safety and implementation results of the strategies aimed at the safe prescription of medications in university hospitals in adult patients. Systematic review - Navarro Cárdenas, Jaime David; Alarcón Nieto, María Cristina; Bernal Vargas, María Paula; Estrada-Orozco, Kelly; Gaitán Duarte, Hernando (Colombian Journal of Anesthesiology, 2021)
Introduction: A broad range of practices aimed at improving the effectives and safety of this process have been documented over the past few years. Objective: to establish the effectiveness, safety and results of the implementation of these strategies in adult patients in university hospitals. Methodology: A review of systematic reviews was conducted, in addition to a database search in the Cochrane Library of Systematic Reviews, Embase, Epistemonikos, LILACS and gray literature. Any strategy aimed at reducing prescription-associated risks was included as intervention. This review followed the protocol registered in the International Prospective Registry of Systematic Reviews (PROSPERO): CRD42020165143. Results: 7,637 studies were identified, upon deleting duplicate references. After excluding records based on titles and abstracts, 111 full texts were assessed for eligibility. Fifteen studies were included in the review. Several interventions grouped into 5 strategies addressed to the prescription process were identified; the use of computerized medical order entry systems (CPOE), whether integrated or not with computerized decision support systems (CDSS), was the most effective approach. Conclusions: The beneficial effects of the interventions intended to the prescription process in terms of efficacy were identified; however, safety and implementation results were not thoroughly assessed. The heterogeneity of the studies and the low quality of the reviews, preclude a meta-analysis.